Transparency of information on halal hospitality service in accommodation websites / Nor Hidayatun Abdul Razak … [et al.] - Abdul Razak, Nor Hidayatun; Abd Wahab, Rahimah; Abd Jabar, Faizan; Mohd Burhan, Norhapizah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
In order to attract halal oriented consumers to use the halal hospitality service, accommodation providers should inform the potential consumers of the relevant facilities and services being offered. In utilizing the capacity of websites, the display of appropriate information will trigger the interest of consumers to surf the providers’ websites. However, the transparency of information provided is important since it gives impact on consumers’ trust. Thus, this study aimed to explore the transparency of information provided on halal services via the platform of accommodation websites. This study focused on the current approaches of accommodation providers in providing halal information online and propose appropriate ways to improve the quality of information provided. This study therefore, is significant as it strengthens knowledge among industry players in their quest to market halal services to specific target consumers.